Analisis Kemampuan Koneksi Matematis Siswa Berbasis Etnomatematika Uma Jompa - Qonitah Qonitah; Al Kusaeri (PT. Pusmedia Group Indonesia, 2024)
This study aims to analyze the mathematical connection ability of Uma Jompa ethnomathematics-based students at SMA Darul Furqan Bima City. The ethnomathematics approach was chosen because of its potential in integrating local culture into mathematics learning, thus making learning more relevant and meaningful. This study uses a qualitative approach with three students categorized based on their levels of mathematical ability, namely high, medium, and low. The results showed that students with high categories were able to solve mathematical problems systematically with in-depth understanding, while students in the medium category needed more time and guidance to develop structured solution steps. The low category students showed basic understanding, but were less thorough and systematic in solving problems. Problem-based learning approaches and scaffolding are identified as effective strategies to support the development of students' mathematical connections at different levels of ability. The integration of Uma Jompa culture into mathematics learning has been proven to help students connect mathematical concepts with real contexts, while strengthening local cultural identity. This research provides important implications for the development of culturally and contextual mathematics learning strategies.